Analisis Dampak Psikologis Korban Love Scam - Segara, I G Bayu Candra; Chusniyah, Tutut; Dharmastuti, Anjarie (Universitas Negeri Malang, 2025)
The phenomenon of love scams, or online dating fraud, has become a crucial issue in the realm of digital crime that capitalizes on individuals' emotional vulnerability, especially through social media platforms and dating sites. This research aims to analyze the psychological impact on victims of such scams, using a descriptive qualitative approach and a literature review. The study results show that victims of love scams not only experience significant financial losses but also face deep emotional trauma, such as post-traumatic stress disorder (PTSD), depression, feelings of shame, loss of self-confidence, and suicidal ideation. Findings also indicate that the majority of victims are middle-aged women with a high level of education and a tendency towards impulsivity and affective dependency. The long-term process of deception leads to a complex psychological attachment to the perpetrator, worsening the victim's mental state. In addition, this deception has a systemic impact on the victim's social status and interpersonal relationships. This study recommends in-depth professional psychological interventions and multidimensional prevention strategies to reduce the prevalence and long-term impact of digital romance scams. AbstrakFenomena love scam atau penipuan kencan daring telah menjadi isu krusial dalam ranah kejahatan digital yang memanfaatkan kerentanan emosional individu, khususnya melalui platform media sosial dan situs kencan. Penelitian ini bertujuan untuk menganalisis dampak psikologis yang dialami oleh korban penipuan tersebut, dengan pendekatan kualitatif deskriptif melalui studi literatur . Hasil studi menunjukkan bahwa korban love scam tidak hanya mengalami kerugian finansial yang signifikan, tetapi juga menghadapi trauma emosional mendalam, seperti gangguan stres pascatrauma (PTSD), depresi, perasaan malu, kehilangan kepercayaan diri, hingga ingin bunuh diri. Temuan juga mengindikasikan bahwa mayoritas korban merupakan perempuan setengah baya dengan tingkat pendidikan tinggi dan kecenderungan impulsif serta ketergantungan afektif. Proses penipuan yang berlangsung dalam jangka waktu panjang menyebabkan keterikatan psikologis yang kompleks terhadap pelaku, sehingga memperburuk kondisi mental korban. Selain itu, penipuan ini berdampak sistemik terhadap status sosial dan hubungan interpersonal korban. Penelitian ini merekomendasikan intervensi psikologis profesional yang mendalam serta strategi pencegahan multidimensi guna mengurangi prevalensi dan dampak jangka panjang dari penipuan asmara digital.